Lipidomic analysis of moss species Bryum pseudotriquetrum and Physcomitrium patens under cold stress. Issue 6 (22nd December 2022) - Lu, Yi; Eiriksson, Finnur Freyr; Thorsteinsdóttir, Margrét; Simonsen, Henrik Toft
Abstract: Bryophytes, which lack lignin for protection, support themselves in harsh environments by producing various chemicals. In response to cold stress, lipids play a crucial role in cell adaptation and energy storage. Specifically, bryophytes survive at low temperatures by producing very long‐chain polyunsaturated fatty acids (vl‐PUFAs). The in‐depth understanding of the lipid response to cold stress of bryophytes was studied by performing lipid profiling using ultra‐high‐performance liquid chromatography‐quadrupole time of flight mass spectrometry (UHPLC‐QTOF‐MS). Two moss species ( Bryum pseudotriquetrum and Physcomitrium patens ) cultivated at 23°C and at 10°C were included in this study. Relative quantitative lipid concentrations were compared and the potential lipid biomarkers were identified by multivariate statistical analysis in each species. In B. pseudotriquetrum, it was observed that the phospholipids and glycolipids increased under cold stress, while storage lipids decreased. The accumulation of the lipids with high unsaturation degrees mostly appears in phospholipids and glycolipids for both mosses. The results also indicate that two unusual lipid classes in plants, sulfonolipids and phosphatidylmethanol are biosynthesized by the bryophytes. This has not been seen previously and show that bryophytes have a very diverse chemistry and substantially different from other plant groups. Abstract : During cold stress hundreds of lipids were identified with high quality MS/MS spectrums in moss Bryum pseudotriquetrum and Physcomitrium patens . The lipidomes of B. pseudotriquetrum is reported for the first time, along with several unusual lipids.